Avaliação da acessibilidade no ensino superior: UTFPR - Câmpus Medianeira - Baú, Marlene Alamini [UNESP] (2015)
Due to the increased number of disabled students in higher education, as well as the concern to ensure your rights, we need to know how institutions are organizing to respond to the needs of these students. Thus, this study aimed, by means of two studies, analyze the accessibilities conditions and the satisfaction level of the disabled students. The first study aimed to identify and evaluate the accessibility conditions in the UTFPR campus Medianeira. This step was performed using for the research, the Instrument for Assessment of Accessibility Conditions in Higher Education Institutions, composed of nine items representing 11 pre-defined routes. The application of the protocol, identified the missing items and the elements that could difficult the displacement of disabled students on each route assessed. The results showed that the architectural structure of the university, although the absence of some elements, was sufficient to ensure the accessibility of disabled students or reduced mobility, in their dependencies. The second study aimed to evaluate the satisfaction and dissatisfaction of four disabled students enrolled in the institution. To collect the data was applied to A and C part of the Satisfaction Scale and Attitudes of Disabled People - ESA. The data allowed to measure and get the opinion of the students about the operational, psychoaffective and structural satisfaction, and their attitudes face of the obstacles. The final result showed that although two items relating to physical structure does not fully meet current regulations, in the general context, the disabled students had full satisfaction about the accessibility at the university.